Sustainable Enviromental Management dalam Mengatasi Permasalahan Kerusakan Lahan Akibat Penambangan Galian C di Kabupaten Karangasem - Nyoman Sumawdiayani (Program Studi Administrasi Negara, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Warmadewa, 2021)
The topography of Karangasem Regency is very varied, in the form of plains, hills, mountains, namely the highest mountain in Bali (Gunung Agung). The location of Karangasem Regency which is close to Mount Agung causes Karangasem Regency to have a wealth of natural resources in the form of class C minerals, namely sand and rocks which are abundant compared to other regencies in Bali. The government of Karangasem Regency collects taxes on group C mining entrepreneurs. Exploitation of land in Karangasem Regency carried out by C mining entrepreneurs has a negative impact, namely environmental damage. The purpose of this study was to determine the implementation of Sustainable environmental management in overcoming the problem of land damage due to excavation c mining in Karangasem Regency. The research method used is the library research method. The results of the study showed that there was critical land due to mining business activities of C excavation which did not carry out land reclamation after post-mining. This is because the C mining entrepreneurs in Karangasem Regency do not carry out the basic principles of Sustainable Environmental Management, namely the principle of Intragenerational equity, the principle of intergenerational equity, the principle of preventive action, the principle of prudence, the precautionary principle and the polluter-pays principle.